Analisis Karya “Kilau Harapan” Sebagai Kritik Sosial - Fenita Risma Wardhani; Dyah Yuni Kurniawati (Penerbit dan Percetakan, CV. Picmotiv, 2026)
This study examines the visual interpretation of the fairy tale The Little Match Girl by Hans Christian Andersen in a relief print artwork entitled “Kilau Harapan”. The artwork addresses issues of poverty, child neglect, and escapism through a symbolic and surreal visual approach. This study aims to examine the relationship between visual elements, symbolism, and the social criticism represented in the artwork. The research employs a descriptive qualitative method using Edmund Burke Feldman’s art criticism approach, which consists of description, formal analysis, interpretation, and evaluation. Data were collected through artwork observation, visual documentation, and literature review related to visual interpretation, semiotics, and relief printmaking. The findings show that Kilau Harapan represents the emotional experiences of the main character through visual symbols such as matchlight, golden threads, and imaginative worlds as forms of hope and escape from harsh social realities. Beyond its aesthetic value, the artwork also implicitly conveys social criticism regarding poverty and child neglect through a symbolic and emotional visual approach